1963
DOI: 10.1021/jf60127a023
|View full text |Cite
|
Sign up to set email alerts
|

Soil Adsorption of Herbicides, Adsorption of Serveral Pre-emergence Herbicides by Hawaiian Sugar Cane Soils

Abstract: est to measure the respiration rates of the fumigated and unfumigated termites. The results of this experiment showed a definite increase in the rate of oxygen uptake in the case of the fumigated insect. The respiratory quotient was increased from 0.5 to 1.0. The fluoride probably disrupts the basic energetics of the cell in some manner

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…On the other hand, of the amounts initially adsorbed on Melfort loam, about of linuron and chlorbromuron, 507o of diuron and metobromuron,2'77a of monolinuron and 8Vo of monuron were still adsorbed even after five rinses (Fig. 3C) On the basis of the ft and Q values at C : l, the general order of the increasing adsorption of the seven urea herbicides o-n the five prairie soils was similar to that reported by Hilton and Yuen (1963) for Hawaiian soils and Hance (1965), Briggs (1969), and Osgerby (1970) for several British soils. The inverse relationship between the water solubility of the six phenylureas and their extent ol adsorption was in agreement only with the earlier observations of Hilton and Yuen (1963).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…On the other hand, of the amounts initially adsorbed on Melfort loam, about of linuron and chlorbromuron, 507o of diuron and metobromuron,2'77a of monolinuron and 8Vo of monuron were still adsorbed even after five rinses (Fig. 3C) On the basis of the ft and Q values at C : l, the general order of the increasing adsorption of the seven urea herbicides o-n the five prairie soils was similar to that reported by Hilton and Yuen (1963) for Hawaiian soils and Hance (1965), Briggs (1969), and Osgerby (1970) for several British soils. The inverse relationship between the water solubility of the six phenylureas and their extent ol adsorption was in agreement only with the earlier observations of Hilton and Yuen (1963).…”
supporting
confidence: 83%
“…The adsorption of a number of urea herbicides has been studied in a variety of soils. However, the adsorptive behavior of most of these herbicides has been studied either singly or in combination with selected members of other classes of herbicides, with only a few studies on the urea herbicides as a group (Hilton and Yuen 1963;Hance 1965;Briggs 1969;Osgerby 1970 Hilton and Yuen (1963) and Hance (1967) 7)E itr ts: For personal use only. (Fig.…”
mentioning
confidence: 99%
“…The adsorptive properties of soil chars were first proposed by Hilton and Yuen (1963) who reported that the sorption of substituted urea and S-triazine herbicides by Hawaiian sugarcane soils which had routinely been burned to remove cane trash remained high after removal of soil organic matter by hydrogen peroxide. Sorption of these herbicides was reduced markedly, however, after igniting the soils.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of chars binding organic contaminants such as the precursor of atrazine, s-triazine, was stated by Hilton and Yuen ( 1963 ). They discovered that the retained sorptivity of many Hawaiian soils for s-triazines was a result of the soil chars arising from burning of sugarcane trash.…”
Section: Applicationsmentioning
confidence: 99%